Crystallochemical Study of Kaolinitic Minerals from Anambra And Ebonyi States of Southeastern Nigeria - C.J.O, Anarado,; A.N, Eboatu,; C.E, Anarado,; C.I., Egwuatu, (IJRDO-Journal of Applied Science, 2016)
The major deposits of Kaolinitic mineral were sampled, with the aim of studyingpossible solid solution, ionic substitution, and thus, ultimately understanding thethe nature and sizes of nanoparticles in the mineral deposits. Powder X-rayDiffraction Analysis, X-ray Flourescence analysis and Physical tests were used tostudy them. Kaolinite and Quartz were the major phases in the raw AnambraKaolin, while the Ebonyi Kaolin had Kaolinite, Quartz, Cristobalite,Montmorillonite and Goethite as major phases. The quartz were deposited inhexagonal crystalline structure, with cell parameters : a- 4.91239A, b-4.91239A,c-5.40385A. The Kaolinite had Monoclinic structure, with cell parameters: a5.16000A,b-8.95232A, c-7.39000A. Cristobalite had Cubic structure, witha,b,c,=7.16000A. Montorillonite had hexagonal structure, with a-5.21000A, b5.21000A,c-22.00000A. Goethite had Orthorhombic structure, with a-4.61880A,b-9.95280A, c-3.02360A. The Specific Gravity of the Anambra deposite was 2.2,while that of Ebonyi was 2.6. Both had relatively low Moh’s hardness value of 1.0.While the Anambra deposit showed white streak, the Ebonyi deposit showedYelllowish brown streak. The Anambra deposit had the major oxides as -Al2O3 =27.71%, SiO2 = 65.76, giving a ratio of 2.37, while the Ebonyi deposit had Al2O3=5.22, SiO2 =77.05, with a ratio of 14.76. Both ionic substitution and solidsolution occurred in the Ebonyi deposit. Montmorillonite has replaced someQuartz in its hexagon structure, instead of the usual Monoclinic structure. TheKaolinite also had a Triclinic structure instead of hexagonal structure expected.The industrial application of these minerals would be significantly impacted by thenano-structural changes.